HELPING THE ELEMENTARY CLASSROOM TEACHER TO INCLUDE SCIENCE IN HER PROGRAM. (Science Education, 1955)
The article presents a report about the panel discussion at the National Council for Elementary-Science meetings in Saint Paul, Minnesota. Clarence Boeck, chairman of the council, said that science teaching in the elementary school is important in the education. Mildred Brandenberger explained that teachers want to find out what is important for children to know. Theodore Johnson told about the area workshops in Saint Paul. Jerome Leavitt suggested that principles should stimulate their teacher's interests in science teaching by having materials available.